The Influence Of Internship Experience, Career Interest, And Soft Skills On The Work Readiness Of 2020 Pgri Semarang University Students - Auliya Minaka, Muhammad Rizqi; Sutrisno,; Rr. Hawik Ervina Indiworo, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to analyze the factors influencing the job readiness of 2020 students from the Faculty of Economics and Business, Faculty of Engineering and Informatics, and Faculty of Law at PGRI Semarang University. The research sample consists of 100 respondents from these faculties. Data collection was conducted using a questionnaire distributed via Google Forms employing a Likert scale. The data were analyzed using the method of multiple linear regression analysis through SPSS 27. The results indicate that job readiness is influenced by internship experience, career interest, soft skills, and hard skills. The obtained F-value is 22.930 with a significance value of 0.000 < 0.05, indicating that internship experience, career interest, soft skills, and hard skills collectively have a significant impact on students' job readiness. Furthermore, the t-test results for internship experience (t = 2.503), career interest (t = 5.107), and soft skills (t = 8.345) show that these variables have a positive and significant partial effect on the job readiness of students from the Faculty of Economics and Business, Faculty of Engineering and Informatics, and Faculty of Law at PGRI Semarang University, batch of 2020.